The Effect of Population and Investment on Gross Regional Domestic Product and Unemployment in East Kalimantan Province - Yuli Hardiyanti; Jiuhardi; Juliansyah Roy (Journal of International Multidisciplinary Research, 2026)
This study analyzes the effect of population and investment on the Gross Regional Domestic Product (GRDP) and unemployment in East Kalimantan Province during the 2016–2025 period. The research employs a quantitative explanatory design using secondary time-series data obtained from Statistics Indonesia (BPS) of East Kalimantan. Path analysis was applied through two structural equations using SPSS 21, complemented by the Sobel test to examine the mediating role of GRDP. The results show that population and investment each have a positive and significant direct effect on GRDP, and jointly explain 97.4% of its variation. GRDP, in turn, has a negative and significant effect on unemployment, accounting for 76.3% of its variation. The Sobel test confirms that GRDP significantly mediates the indirect effects of both population (Z = 2.295) and investment (Z = 2.628) on unemployment. These findings indicate that economic growth, as reflected in GRDP, acts as a strategic transmission channel converting demographic potential and capital accumulation into employment opportunities, thereby reducing unemployment in the region.